Detection of handwritten text using convolutional neural network - Jasim, Rabib Bin; Mahin, Rokeya Sultana (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.